Bank Ownership Type and Banking Relationships - Berger, Allen N.; Klapper, Leora F.; Martinez Peria, Maria Soledad; Zaidi, Rida (World Bank, Washington, DC, 2012)
The authors formulate and test hypotheses about the role of bank ownership types-foreign, state-owned, and private domestic banks-in banking relationships, using data from India. The empirical results are consistent with all of their hypotheses with regard to foreign banks. These banks tend to serve as the main bank for transparent firms, and firms with foreign main banks are most likely to have multiple banking relationships, have the most relationships, and diversify relationships across bank ownership types. The data are also consistent with the hypothesis that firms with state-owned main banks are relatively unlikely to diversify across bank ownership types. However, state-owned banks often do not provide the main relationship for firms they are mandated to serve (for example, small, opaque firms), and the predictions of negative effects on multiple banking and number of relationships hold for only one type of state-owned bank.